Use of Financial Emergency Aid for adults with type 1 diabetes during COVID-19 pandemic in Brazil, 2020 - Reis, Aline Leão (2022)
Objective: We sought to analyze the use of financial emergency aid in the acquisition of inputs for treatment by adults with Type 1 Diabetes during social distancing due to the pandemic of COVID-19 in Brazil. Method: Cross-sectional survey carried out during July 2020, in Brazil, using an online form about socioeconomic, demographic, glycemic monitoring and input acquisition. Pearson's Chi-Square test was applied, with adjusted residual analysis (p<0.05). Results: 472 adults participated, of which 39.19% reported having received emergency financial aid from the Federal Government. Receiving the aid was associated with not having higher education (p<0.000), living in peripheral neighborhoods (p<0.000), having reduction in income during the pandemic (p=0.001) and having a family income of up to 2 minimum wages (p=0.000). Most participants used the aid to pay basic bills (57.5%) and purchase food (43.8%). Conclusion: Using the aid to buy treatment supplies was associated with purchasing them with their own money or by donation and not spending the aid with supplies was associated with purchasing them through the Unified Health System (Sistema Único de Saúde - SUS). Financial emergency aid was used to purchase essential supplies for treatment and basic needs, especially for people with worse socioeconomic conditions and who were unable to acquire these materials through SUS.